2020
DOI: 10.1101/2020.01.20.913426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vegetation and seed bank dynamics highlight the importance of post-restoration management in sown grasslands

Abstract: Sowing grass seeds generally supports the rapid development of a closed perennial vegetation, which makes the method universally suitable for fast and effective landscape-scale restoration of grasslands. However, sustaining the recovered grasslands, and increasing their diversity is a challenging task. Understanding the role of seed bank compositional changes and vegetation dynamics contributes to designating management regimes that support the establishment of target species and suppress weeds. Our aim was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In addition, miscellaneous grasses increased the number of OTU species (Figure 4). In agreement with these results, Valkó et al (2020) reported that the planting of gramineous grasses was beneficial to the growth of perennials. This could have occurred by effectively changing the community structure of soil microorganisms (Zhu et al, 2020) and by promoting various species of rhizosphere ANF microbial populations (Minamisawa et al, 2004;Miyamoto et al, 2004;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, miscellaneous grasses increased the number of OTU species (Figure 4). In agreement with these results, Valkó et al (2020) reported that the planting of gramineous grasses was beneficial to the growth of perennials. This could have occurred by effectively changing the community structure of soil microorganisms (Zhu et al, 2020) and by promoting various species of rhizosphere ANF microbial populations (Minamisawa et al, 2004;Miyamoto et al, 2004;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Deferred grazing from spring to autumn and rotational grazing increased the soil seed bank of perennial and annual grasses (Nie et al 2015). However, soil seed banks made limited contributions to the maintenance of plant biodiversity in both mown and abandoned sites on the Great Hungarian Plain (Valko et al 2020).…”
Section: Introductionmentioning
confidence: 99%